Impact of the 21-gene expression assay on treatment decisions and clinical outcomes in breast cancer with one to three positive lymph nodes - Li, Guan-Qiao; Xie, Shang-Jin; Wu, San-Gang; He, Zhen-Yu (Frontiers in Endocrinology, 2023)
Background: To assess the practice patterns of the recurrence score (RS) based on the 21-gene expression assay on adjuvant chemotherapy recommendations and survival outcomes in estrogen receptor-positive (ER+)/HER2- breast cancer (BC) with 1-3 positive lymph nodes (N1). Methods: We included patients with T1-2N1M0 and ER+/HER2- BC diagnosed between 2010 and 2015 in the Surveillance, Epidemiology, and End Results Oncotype DX Database. Breast cancer-specific survival (BCSS) and overall survival (OS) were assessed. Results: We included 35137 patients in this study. There were 21.2% of patients who had RS testing in 2010 and was significantly increased to 36.8% in 2015 (P<0.001). Performance of 21-gene testing was associated with older age, lower tumor grade, T1 stage, lower number of positive lymph nodes, and progesterone receptor-positive disease (all P<0.05). In those without 21-gene testing, age was the main factor significantly related to the receipt of chemotherapy, while RS was the main factor significantly related to chemotherapy receipt in those with 21-gene testing. The probability of chemotherapy receipt in those without 21-gene testing was 64.1% and was decreased to 30.8% in those with 21-gene testing. On multivariate prognostic analysis, the performance of 21-gene testing was associated with better BCSS (P<0.001) and OS (P<0.001) compared to those without 21-gene testing. Similar results were found after propensity score matching. Conclusions: 21-gene expression assay is frequently and increasingly used for chemotherapy decision-making in ER+/HER2- BC with N1 disease. Performance of 21-gene testing is associated with improved survival outcomes. Our study supports the routine use of 21-gene testing in the clinical practice of this population.